Profile of Skin Prick Test in Urticaria Patients: 5 Years Retrospective Study at Dermatology and Venereology Polyclinic, Dr. Moewardi General Hospital, Surakarta, Indonesia - Winda Wijayanti; Annisa Fildza Hashfi; Muhammad Eko Irawanto; Triasari Oktavriana (HM Publisher, 2023)
Background: Urticaria is a skin disorder due to the release of mast cell mediators, which is characterized by raised skin (urtica) accompanied by itching. Skin prick test (SPT) is a rapid, sensitive test for detecting IgE-mediated allergic disease. This study aimed to determine the profile of SPT in urticaria patients. Methods: A descriptive observational study involving 67 research subjects retrospectively using medical record data for the period January 2017-June 2022. Univariate data analysis was carried out in this study with the help of SPSS version 25 software. Results: A total of 67 urticarial patients with positive results on the SPT investigation found that there were more women (71.64%) than men (28.36%), with the most age group being 16-25 years old with 16 patients, followed by 13 patients aged 56-65 years, 12 patients aged 46-55 years, 10 patients aged 36-45 years, 9 years of 26-35 years, 5 patients aged ≥ 65 years and the last age group, namely ≤ 15 years of age in 2 patients. Distribution of urticaria with the most locations in the generalized region, with as many as 20 patients (29.85%), followed by the extremity region with as many as 18 patients (26.87%), the facial region with as many as 17 patients (25.37%) and the least location in the trunk region as many as 12 patients (17.91%). Allergen tests that caused the most were house dust in 21 patients (11.86%), crabs in 18 patients (10.17%), and egg yolk in 11 patients (6.21%). Conclusion: Skin prick test profile at the dermatology and venereology polyclinic, Dr. Moewardi General Hospital, Surakarta, Indonesia, for the period January 2017-June 2022, where the results obtained were that there were more women than men, the largest age group was 16-25 years, the most common distribution of urticaria locations was found in the generalized region and the most common allergens caused by house dust.